Antioxidant Potential of Indian Gooseberry (Emblica officinalis) Paste in Chicken Meatballs - Abinayaselvi, R.; Santhi, D.; Kalaikannan, A.; Natarajan, A.; Nandhini, K. (Journal of Meat Science, 2022)
The aim of the study was to evaluate the antioxidant potential of Indian gooseberry (Emblica officinalis) paste in chicken meatballs and its effect on physicochemical and sensory properties. Chicken meatballs were prepared with the inclusion of Indian gooseberry paste (GBP) at 0, 12%, 15%, and 18% levels. The emulsion pH, product pH, emulsion stability, and product yield were determined. DPPH Scavenging Activity (%) was studied to establish the antioxidant potential of the GBP in the product. Sensory properties were evaluated using 8 points hedonic scale. Emulsion pH and Product pH decreased significantly (P<0.05) with the addition of GBP. Product yield decreased significantly (P<0.05) with the addition of GBP for 15% and 18% levels. DPPH scavenging activity significantly (P<0.01) increased with an increase in the GBP inclusion level, where 18% treatment had the highest antioxidant potential followed by 15% and 12% treatments. The sensory scores for control and 12% treatment were comparable and significantly (P<0.05) lower for 15% and 18% treatments. From this study, it was observed that Indian gooseberry paste could be added as a potential antioxidant in the chicken meatballs, up to a level of 12% without affecting the sensory qualities of the product.